IMPLEMENTASI ASPEK PERPAJAKAN PADA KOPERASI DI KABUPATEN JENEPONTO - Harini Lestari; Mursalim Laekkeng; Andi Nurwanah (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the implementation of the taxation aspects of cooperatives in Jeneponto Regency. The analysis method used is descriptive qualitative analysis method, namely describing, analyzing, and explaining the implementation of taxation aspects in cooperatives in Jeneponto Regency based on the applicable taxation provisions to get a clear and comprehensive picture of the taxation aspects of each cooperative. The results of this study indicate that the implementation of the taxation aspects of the cooperative in Jeneponto Regency is in accordance with the self-assessment system referring to existing tax regulations, both in the calculation and withholding of taxes. However, the self-assessment system has not been implemented optimally by cooperatives. Cooperatives in Jeneponto Regency in fulfilling their payable tax obligations are still forced through a summons from the tax officer. Cooperatives in Jeneponto Regency apply Final Income Tax based on Peraturan Pemerintah Nomor 23 Tahun 2018 and Income Tax on Remaining Business Results based on Peraturan Menteri Keuangan Nomor 111 / PMK / 03/2010.